Detection of Oxidative Stress Induced by Nanomaterials in Cells-The Roles of Reactive Oxygen Species and Glutathione - Čapek, Jan; Roušar, Tomáš (MDPI, 2021)
The potential of nanomaterials use is huge, especially in fields such as medicine or industry. Due to widespread use of nanomaterials, their cytotoxicity and involvement in cellular pathways ought to be evaluated in detail. Nanomaterials can induce the production of a number of substances in cells, including reactive oxygen species (ROS), participating in physiological and pathological cellular processes. These highly reactive substances include: superoxide, singlet oxygen, hydroxyl radical, and hydrogen peroxide. For overall assessment, there are a number of fluorescent probes in particular that are very specific and selective for given ROS. In addition, due to the involvement of ROS in a number of cellular signaling pathways, understanding the principle of ROS production induced by nanomaterials is very important. For defense, the cells have a number of reparative and especially antioxidant mechanisms. One of the most potent antioxidants is a tripeptide glutathione. Thus, the glutathione depletion can be a characteristic manifestation of harmful effects caused by the prooxidative-acting of nanomaterials in cells. For these reasons, here we would like to provide a review on the current knowledge of ROS-mediated cellular nanotoxicity manifesting as glutathione depletion, including an overview of approaches for the detection of ROS levels in cells.
Detekce oxidačního stresu indukovaného nanomateriály v buňkách - Role reaktivních forem kyslíku a glutationu
Keywords: reactive oxygen species; oxidative stress; glutathione; nanotoxicity; cell injury; fluorescence probes; reaktivní formy kyslíku; oxidativní stres; glutathion; nanotoxicita; buněčné poškození; fluorescenční sondy